Sur la plage emmêlés : Celtes, Ligures, Grecs et Ibères dans la confrontation des textes et de l’archéologie - Philippe Boissinot (Mélanges de la Casa de Velázquez, 2005)
An excessively fundamentalist conception of ethnic identity is undoubtedly an obstacle to an understanding of the relations among the communities settled in southern France in Roman times. Multiculturalism is no modern phenomenon; it was equally present in the societies that evolved along the Mediterranean littoral, mingling Greeks, Celts, Ligurians and Iberians. In order to grasp this reality it is essential to avoid the drawing of inelastic borderlines; one must adopt a more flexible definition of ethnicity and eschew the academic dichotomy between Greeks and non-Greeks. Whenever possible, it is vital to introduce the histories of social agents who stand on the margins of accepted belonging.